Preventive effect of Euphorbia royleana Boiss on diabetes induced by streptozotocin via modulating oxidative stress and deoxyribonucleic acid damage. (2nd October 2021) - Zafar, Mehroz; Sharif, Ali; Khan, Darosham; Akhtar, Bushra; Muhammad, Faqir; Akhtar, Muhammad Furqan; Fatima, Tuktum
Abstract: Oxidative stress is associated with streptozotocin induced diabetes. The present study was conducted to investigate the anti-oxidant, anti-diabetic and genotoxic effects of Euphorbia royleana Boiss. stem's crude extract in rats. Better inhibitory concentration (IC50 ) of methanolic extract in alpha amylase and antioxidant assays along with improvement in hyperglycemia can be linked with the presence of phenolic acids and flavonoids determined quantitatively by HPLC. The declining superoxide dismutase, catalase activities, and hydrogen peroxide concentrations were restored at the dose of 500 mg/kg. The methanolic extract turned out to be Class I genotoxic at 100 µg/mL. Moreover, improvement in histopathological changes of pancreas, liver and kidney were also observed.